High-precision measurement of the x-ray Cu Kα spectrum. (12th May 2017) - Mendenhall, Marcus H; Henins, Albert; Hudson, Lawrence T; Szabo, Csilla I; Windover, Donald; Cline, James P
Abstract: The structure of the x-ray emission lines of the Cu K α complex has been remeasured on a newly commissioned instrument, in a manner directly traceable to the Système Internationale definition of the meter. In this measurement, the region from 8000 to 8100 eV has been covered with a highly precise angular scale, and well-defined system efficiency, providing accurate wavelengths and relative intensities. This measurement updates the standard multi-Lorentzian-fit parameters from Härtwig, Hölzer, et al, and is in modest disagreement with their results for the wavelength of the K α 1 line when compared via quadratic fitting of the peak top; the intensity ratio of K α 1 to K α 2 agrees within the combined error bounds. However, the position of the fitted top of K α 1 is very sensitive to the fit parameters, so it is not believed to be a robust value to quote without further qualification. We also provide accurate intensity and wavelength information for the so-called K α 3, 4 'satellite' complex. Supplementary data, available online atstacks.iop.org/JPB/50/115004/mmedia, is provided which gives the entire shape of the spectrum in this region, allowing it to be used directly in cases where simplified, multi-Lorentzian fits to it are not sufficiently accurate.